Super-parenting for ADD : an innovative approach to raising your distracted child - Hallowell, Edward M.; Jensen, Peter S. (New York : Ballantine Books, 2008)
Drs. Hallowell and Jensen put the talents, charms, and positive essence of your child ahead of any presumed shortcomings. This book shows you how to unwrap the wonderful, surprising gifts of ADD and turn what is too often labeled a lifelong disability into a lifelong blessing.
Originally published in hardcover in the United States by Ballantine Books, c2008.
Includes bibliographical references (p. 194-202) and index.
Keywords: Attention-deficit hyperactivity disorder; Child rearing; Parenting